Development of Simplified Models of Doubly-Fed Induction Generators (DFIG). A contribution towards standardizedmodels for voltage and transient stability analysis - Michael, Snyder (My University, 2012)
With the increasing amounts of wind power being installed on electrical grids, the characterization of wind turbines during all operating conditions is essential for systemoperators to ensure security and stability for their customers. This characterization must be achieved by appropriate models of various wind turbine technologies that can accurately depict the interaction between wind turbines and the interconnected power system. Of critical importance and the focus of this thesis is the response of wind turbines during a grid fault, and specifically the wind turbines’ effect on voltage and transient stability through the control of reactive power (Q) support. The DFIG wind turbine is the focus of this thesis, as it presents a more complicated model and response to transient events and thus warrants further research in the pursuit of a standardized simplified model for the purposes of voltage and transient stability analysis. The proposed model is developed specifically for dynamic simulations in PSS/E power system simulation tool, which is a positive-sequence phasor time-domain analysis. The simulation tool is limited to a 10ms time step. Therefore there is a need to simplify the model to a level that can be depicted at this granularity but also maintain a fast simulation time for implementation in large network analyses. A 5th order model of the DFIG wind turbine is introduced through the fundamental electrical equations that describe the machine. The control of the machine is described, including the use of an active power (P) controller, reactive power (Q) controller, a rotor speed controller, and a torque controller. A rotor voltage limitation is imposed and the effects are studied. The stability of the DFIG with current controller is analyzed. The DFIG is recognized as a poorly damped machine with poles naturally occurring near the line frequency (50 Hz). These poorly damped poles are further evaluated through sensitivity analyses of model parameters and controller settings. A flux damping term is discussed and implemented in the DFIG detailed model. The results show successful damping for small disturbances but a high sensitivity to grid voltage dips. The DC-chopper protection of the DFIG rotor circuit is analyzed. A simplified model for the DCchopper protection is proposed that neglects the DC-link voltage controller and the control of the grid-side converter but instead focuses on the effects of the rotor-side converter losing controllability and entering into diode rectifier operation. Any imbalance of rotor circuit power and grid-side converter power is assumed to be effectively burned in the DC crowbar via a properly controlled DC-chopper and DC-link voltage. The 5th order model is compared to a more detailed model developed in PSCAD. In previous research [1], the PSCAD model has been validated against field measurements for a DFIG wind turbine experiencing both a shallow and deep voltage dip. The 5th order model of this thesis shows reasonable accuracy to the PSCAD model but is not able to fully synchronize with the model. Step responses of the DFIG machine model in PSCAD was studied and compared to the 5th order DFIG machine designed in Matlab/Simulink to further analyze possible reasons for the differences in the two models. iii The 5th order model is simplified into a set of algebraic equations with a Q controller, based on several assumptions. The goal of the simplified model is for implementation in PSS/E dynamic simulations with fast simulation times in complex power networks. The simplified model is compared to the detailed model and shows reasonable accuracy in depicting the general response to voltage dips for the three operating conditions (sub-synchronous, synchronous, and super-synchronous). The machine is modeled with a fixed rotor speed and compared to the 5th order model with a variable rotor speed.
Keywords: Elkraftteknik; Electric power engineering